Problem niezdolności relatywnej do podjęcia istotnych obowiązków małżeńskich w świetle wyroku Roty Rzymskiej c. Jarawan z 4 października 1995 r. - Góralski, Wojciech (Ius Matrimoniale, 2013)
In the decision of the Roman Rota c. Jarawan the case of invalidity of the marriage due to inability to take up significant marital obligations by the respondent was examined and decided (a negative decision was issued in the first instance and a positive in the second instance). The Rotal judges subjected the decision of the second instance to decisive criticism by, i.a., a few experts, and decided that it indicates the acceptance of relative inability by the court, which is clearly inconsistent with the canonical norm 1095, n. 3 of the Code of Canon Law.